Enhancing Speaking Proficiency by Adapting Grammar- Translation Method And Electronic Dictionary For Young Learners - Edy Suseno; Oikurema Purwati (IJET (Indonesian Journal of English Teaching), 2020)
The young learners are very potential to grow their knowledge earlier. By having sufficient knowledge in their heads, they have a great opportunity to develop any other knowledge. English, however, is an important language in the world. By using English, the students could know more about anything. There are many kinds of method used by teachers to teach young learners to speak English. The teacher is often trying very hard to bring the students into a learning atmosphere. Indeed, Both the teacher and students want to get the expected goal. On the other hand, the condition turns to be uneasy when the students are reluctant to respond to their teacher’s questions as feedback. It is an important part for the teacher to find another method to help students active. Moreover, vocabulary building is an essential part of delivering the intention to others. By having enough vocabulary list in the students’ head, it would ease them to choose the right words to convey. Hence, the use of an electronics dictionary could satisfy the students’ needs. By implementing it while learning grammar and reading, the students could better their vocabulary and pronunciation skills to conduct speaking.